Dissemination and prevalence of plasmid-mediated high-level tigecycline resistance gene tet (X4) - Zhang, Shaqiu; Wen, Jinfeng; Wang, Yuwei; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; Yang, Qiao; Huang, Juan; et al. (Frontiers in Microbiology, 2022)
With the large-scale use of antibiotics, antibiotic resistant bacteria (ARB) continue to rise, and antibiotic resistance genes (ARGs) are regarded as emerging environmental pollutants. The new tetracycline-class antibiotic, tigecycline is the last resort for treating multidrug-resistant (MDR) bacteria. Plasmid-mediated horizontal transfer enables the sharing of genetic information among different bacteria. The tigecycline resistance gene tet(X) threatens the efficacy of tigecycline, and the adjacent ISCR2 or IS26 are often detected upstream and downstream of the tet(X) gene, which may play a crucial driving role in the transmission of the tet(X) gene. Since the first discovery of the plasmid-mediated high-level tigecycline resistance gene tet(X4) in China in 2019, the tet(X) genes, especially tet(X4), have been reported within various reservoirs worldwide, such as ducks, geese, migratory bird, chickens, pigs, cattle, aquatic animal, agricultural field, meat, and humans. Further, our current researches also mentioned virus as novel environmental reservoirs of antibiotic resistance, which will probably become a focus of studying the transmission of ARGs. Overall, this article mainly aims to discuss the current status of plasmid-mediated transmission of different tet(X) genes, in particular tet(X4), as environmental pollutants, which will risk to public health for the “One Health” concept.